2009
DOI: 10.1600/036364409788606352
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the Neotropical Blueberry Genus Disterigma (Ericaceae)

Abstract: Disterigma s. l. comprises 37 species of small shrubs found in Central and South America, mostly in cloud forests and páramos. The notion that the morphological circumscription of Disterigma s. l. is too wide and that it may not be a monophyletic group was supported by recent molecular evidence extracted from only a few species of Disterigma. This study addresses the monophyly and position of Disterigma s. l. within the complex blueberry tribe Vaccinieae through an intensive taxon sampling. Seventy-nine speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 14 publications
2
21
1
1
Order By: Relevance
“…Nuclear and plastid markers indicate that Disterigma is polyphyletic (Pedraza-Peñalosa, 2009). The six sampled páramo species occur in a well-supported Disterigma s.s. clade to which neotropical montane forest Sphyrospermum and central Andean Disterigma species are sister.…”
Section: Neotropical Alpine and Montane Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear and plastid markers indicate that Disterigma is polyphyletic (Pedraza-Peñalosa, 2009). The six sampled páramo species occur in a well-supported Disterigma s.s. clade to which neotropical montane forest Sphyrospermum and central Andean Disterigma species are sister.…”
Section: Neotropical Alpine and Montane Elementsmentioning
confidence: 99%
“…Based on the evidence, it may be concluded that Disterigma entered páramo from cloud forest. The poor resolution within the Disterigma s.s. clade, however, does not allow inference as to the number of colonization events (Pedraza-Peñalosa, 2009). Nevertheless, classification of Disterigma in the neotropical element is justified by molecular data.…”
Section: Neotropical Alpine and Montane Elementsmentioning
confidence: 99%
“…The taxonomic placement of new Vaccinieae is difficult due to the striking disparity between generic-level phylogenetic relationships and current classification systems (Kron et al 2002, Powell and Kron 2003, Pedraza-Peñalosa 2009, 2010). Therefore, to determine the generic placement of the new species, four were included in a comprehensive phylogenetic analysis of neotropical Vaccinieae, based on chloroplast and nuclear sequence data of 91 species (Pedraza-Peñalosa et al 2015).…”
Section: Placement and Phylogenetic Affinities Of New Speciesmentioning
confidence: 99%
“…En general, en la determinación de especies nuevas de Ericaceae el autor emplea el concepto filogenético de especie (Nixon & Wheeler 1990). En el caso de la especie acá descrita, la cual sólo se conoce por un individuo, se debe entender que este individuo es diagnosticable por una combinación única de caracteres y se asume que, en ausencia de más material, representa la variación de la especie.…”
Section: Materiales Y Métodosunclassified